Uma apresentação dos métodos de Pontos Interiores na radioterapia e sua comparação com o método Simplex - Freitas, Paula Renata de Morais Gomes (2017)
This work aims to present the Internal Points Methods and to compare the Simplex Method, when applied in the resolution of problems related to the optimal concentration of radiation in the treatment of cancer through radiotherapy. The optimum concentration is related to the higher intensity of radiation associated with less damage to the vital organs. This dissertation was based on works on radiotherapy treatment, aiming to make a comparison between two methods widely used to find an optimal concentration.